THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON THE PURCHASE DECISION OF SCARLETT COSMETIC WHITENING PRODUCTS - Tulus Pujo Nugroho (Asosiasi Dosen Muda Indonesia, 2023)
This study aims to determine the effect of price and product quality on purchasing decisions for Scarlett Cosmetic Whitening products. To determine the effect of price on purchasing decisions for Scarlett Cosmetic Whitening products, to determine the effect of product quality on purchasing decisions for Scarlett Cosmetic Whitening products, it can influence purchasing decisions simultaneously in using Scarlett Cosmetic Whitening products. The analysis method in this study uses quantitative primary data, the test stages carried out are: validity test, reliability test, normality test, multiple linear regression analysis, heteroscedasticity test, multicollinearity test, t test, f test and coefficient of determination. The data used in this study used primary data obtained by distributing online questionnaires and then processed using SPSS 26. The results of this study indicate that the variable price and product quality have a simultaneous effect on purchasing decisions and the most dominant variable on purchasing decisions is product quality and the results of this research regression are Y = -0.792 + 0.401 X1 + 0.604 X2 + e